2018
DOI: 10.1111/nana.12476
|View full text |Cite
|
Sign up to set email alerts
|

Nationalist cosmopolitanism: the psychology of cosmopolitanism, national identity, and going to war for the country

Abstract: A frequently expressed criticism of cosmopolitanism by liberal nationalist theorists is that its moral universalism is incompatible with national identity and patriotic obligations, defined as obligations to the nation and to fellow nationals. While some scholars of cosmopolitanism agree with this incompatibility argument, others contend that nationalism, cosmopolitanism, and patriotic duties are not rivals. However, few efforts have been made to examine the relationship between cosmopolitanism, nationalism, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 84 publications
1
9
0
1
Order By: Relevance
“…It is negatively connected to islamophobia and dehumanisation (McFarland et al, 2019). Moreover, contrary to the stereotypical view of global identification as in opposition to national identification, studies in Poland and the United States showed that people who feel more closely identified with all humanity also feel more closely identified with their nations and local communities (Bassett & Cleveland, 2019; Bayram, 2019; Hamer & Gutowski, 2009; McFarland et al, 2019). More globalised individuals do not reduce contributions to local groups while increasing contributions to global groups, but rather are overall more generous (Grimalda, Buchan, & Brewer, 2018).…”
Section: Identification With All Humanitymentioning
confidence: 96%
“…It is negatively connected to islamophobia and dehumanisation (McFarland et al, 2019). Moreover, contrary to the stereotypical view of global identification as in opposition to national identification, studies in Poland and the United States showed that people who feel more closely identified with all humanity also feel more closely identified with their nations and local communities (Bassett & Cleveland, 2019; Bayram, 2019; Hamer & Gutowski, 2009; McFarland et al, 2019). More globalised individuals do not reduce contributions to local groups while increasing contributions to global groups, but rather are overall more generous (Grimalda, Buchan, & Brewer, 2018).…”
Section: Identification With All Humanitymentioning
confidence: 96%
“…Even those whom the scale identifies as being cosmopolitan are using a form of banal nationalist language to demonstrate this cosmopolitanism. Bayram (2019), in a study of the psychology of cosmopolitanism and nationalism, comes close to some of the positions taken here. She does not try to separate cosmopolitans and nationalists into two very different classes of person, but she writes of "nationalist cosmopolitanism."…”
Section: Cosmopolitan Methodology and Methodological Nationalismmentioning
confidence: 52%
“…Bayram (2019), in a study of the psychology of cosmopolitanism and nationalism, comes close to some of the positions taken here. She does not try to separate cosmopolitans and nationalists into two very different classes of person, but she writes of “nationalist cosmopolitanism.” She uses data from the World Values Survey (WVS) to show that most people are both nationalist and cosmopolitan.…”
Section: Cosmopolitan Methodology and Methodological Nationalismmentioning
confidence: 52%
See 1 more Smart Citation
“…His study participants generally did not think much of national identity, as English or British, and that they were rather oblivious, indifferent, or even apathetic to national identity. Of the possible reasons discussed, the most relevant here is that some individuals reject their national identities because they would rather embrace broader, supranational categories viewed as more inclusive and less particularistic (Fenton, 2007: 333; see also Bayram, 2019). Self-identity such as citizen of the world may blur boundaries between national ingroup and immigrant outgroup.…”
Section: The Role Of Cosmopolitanismmentioning
confidence: 99%